Lubrication of a flexible piston skirt conjunction subjected to thermo-elastic deformation: A combined numerical and experimental investigation. (January 2014) - Littlefair, B; Cruz, M De La; Mills, R; Theodossiades, S; Rahnejat, H; Dwyer-Joyce, R; Howell-Smith, S
The piston–cylinder conjunction accounts for nearly 50% of all the parasitic frictional losses in an IC engine of which the piston skirt accounts for nearly half of these losses. Consequently, part-circumferential short skirted compliant pistons have become a development trend, particularly for high-performance engines. Another trend has been the use of light weight moving parts to reduce inertial imbalance. This has led to the use of shorter lighter pistons constructed from lower density materials, such as aluminium. These higher power density pistons typically operate at elevated temperatures and undergo significant mechanical and thermal distortions due to the relatively high thermal expansion coefficients. As a result thermo-mechanical distortion of the skirt plays an important role in controlling the clearance gap between the skirt and the liner and makes the analysis, particularly skirt deformation, a computationally intensive procedure. This paper presents a semi-automatic methodology for the prediction of piston skirt thermo-mechanical deflection, which incorporates skirt deformation as well as piston crown compliant contribution to the skirt–liner clearance. This procedure is based on the creation of a compliance matrix and its intricate manipulation, significantly reducing the simulation run times. Integration of this approach with the numerical solution of Reynolds equation leads to an accurate prediction of film thickness. In addition, an array of ultrasonic sensors is used to directly measure the conjunctional lubricant film thickness in a non-invasive manner. The predictions and measurements show good conformance, an approach not hitherto reported in literature.